2018
DOI: 10.1039/c7tc03384b
|View full text |Cite|
|
Sign up to set email alerts
|

An overview of metamaterials and their achievements in wireless power transfer

Abstract: The schematic of metamaterials applied in wireless power transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
77
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(77 citation statements)
references
References 150 publications
0
77
0
Order By: Relevance
“…Amazing possibilities in manipulation of electromagnetic fields with engineered dense distributions of scatterers (metamaterials) have been demonstrated in the last two decades [10][11][12][13]. Extensive research in the area of metasurfaces, thin two-dimensional metamaterials, established a rigorous theoretical approach to arbitrary control reflection and refraction of an incident planewave [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Amazing possibilities in manipulation of electromagnetic fields with engineered dense distributions of scatterers (metamaterials) have been demonstrated in the last two decades [10][11][12][13]. Extensive research in the area of metasurfaces, thin two-dimensional metamaterials, established a rigorous theoretical approach to arbitrary control reflection and refraction of an incident planewave [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials, with unique negative electromagnetic parameters (e.g., negative refraction, permeability and permittivity), have gained extensive research attention due to their original applications in cloaking, waveguide, wireless power transfer, electromagnetic shielding and high-permittivity capacitor, etc. [1][2][3][4][5]. Metamaterials typically consist of artificially periodic array structure with different geometrical configuration (split-ring resonators, wires, fishnet, or cut-wire pairs) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Physical contact of the particles is not required for electrical conduction in composites . It was demonstrated that the electrical conductivity of the composites occurs not only by the inter‐particle contact, but also through electronic emission between the nearest filler particles which are separated by polymer layer by a distance larger than the inter‐particle contact or the distance for electron hopping.…”
Section: Introductionmentioning
confidence: 99%